Mourning Diana : nation, culture and the performance of grief - Kear, Adrian, 1970-; Steinberg, Deborah Lynn (Routledge, 2002)
The death of Diana, Princess of Wales, on September 1 1997, prompted public demonstrations of grief on an almost unprecented global scale. But, while global media coverage of the events following her death appeared to create an international 'community of mourning', popular reacions in fact reflected the complexities of the princess's public image and the tensions surrounding the popular conception of royalty. Mourning Diana examines the events which followed the death of Diana as a series of cultural-political phenomena, from the immediate aftermath as crowds gathered in public. -- Provided by publisher.